Impacts of air pollution on dry eye disease among residents in Hangzhou, China: A case-crossover study. (March 2019) - Mo, Zhe; Fu, Qiuli; Lyu, Danni; Zhang, Lifang; Qin, Zhenwei; Tang, Qiaomei; Yin, Houfa; Xu, Peiwei; Wu, Lizhi; Wang, Xiaofeng; Lou, Xiaoming; Chen, Zhijian; et al.
Abstract: The purpose of this study is to investigate the potential associations between air pollution and dry eye disease (DED). Data of outdoor air pollutants and meteorology as well as outpatient visits for DED were collected. A time-stratified case-crossover approach was used to analyze the associations between ambient air pollutants and outpatient visits for DED. Among the 5062 DED patients studied, 65.45% were female and 34.55% were male. In the single-pollutant model, significant associations were observed between an increase of 10 μg/m 3 in the concentrations of fine-particulate matter with a median aerometric diameter of less than 10 μm (PM10 ), fine-particulate matter with a median aerometric diameter of less than 2.5 μm (PM2.5 ), sulfur dioxide (SO2 ), nitrogen dioxide (NO2 ), and carbon monoxide (CO) and outpatient visits for DED. These results were consistent with those of the multipollutant model. The strongest associations between air pollutants and patient visits were observed during the cold season and in patients aged 21–40. The significant association between air pollutants (PM10, PM2.5, SO2, NO2, and CO) and DED outpatient visits indicates the importance of increased environmental protection. Graphical abstract: Image 1 Highlights: Significant associations between air pollution and dry eye disease were observed. The most susceptible populations were those aged 21–40. The impact of air pollution on dry eye disease was stronger in the cold season. Abstract : Outpatient visits for DED were significantly associated with air pollutants in Hangzhou, China.